Gulf Cooperation Council (GCC) and Regional Integration in Asia - Dr. Debesh Bhowmik (Financial Markets, Institutions and Risks)
In Asia, SAARC (South Asian Association of Regional Cooperation), ASEAN (Association of South East Asian Nations) and GCC (Gulf Cooperation Council) are being considered as an active regional trading blocs although East Asian integration is on primary cooperation stage and BIMSTEC is treated as organised sub-regional trading bloc. The GCC has completed all criterion of economic integration except introduction of a single currency and ASEAN is advancing its optimum stage of monetary integration but the advancement of SAARC is halted by the shock of non-cooperation from Pakistan. Therefore, contribution of GCC in integrating Asian bloc is to scrutinise in a new outlook. In this paper, the author endeavours to show the impact of economic integration of Gulf Cooperation Council (GCC) on the Asian economic integration in the sense that the process of integration of GCC with SAARC and ASEAN can accelerate the criterion of Asian integration process. Therefore, the author used cointegration and vector error correction model among the indicators of trade integration of exports such as Asian export share, intra export share of GCC, export concentration index of GCC, ASEAN’s export with GCC and SAARC’s export with GCC during 1995-2019. Similarly, the author applied same methodology among the trade indicator of imports such as Asian import share, intra import share of GCC, import concentration index of GCC, ASEAN’s import with GCC and SAARC’s import with GCC during the specified period. The findings revealed that Asian export share has long run significant causalities with SAARC and ASEAN export shares to GCC. Intra export share of GCC has long run causalities with SAARC and ASEAN export shares to GCC. The export concentration index of GCC has significant long run causalities with SAARC and ASEAN export shares to GCC respectively. Even, the short run causalities from export concentration index of GCC to intra export share of GCC, export share of ASEAN and SAARC with GCC and the short run causality from ASEAN export share with GCC to export share of Asia and from intra export share of GCC to export share of ASEAN with GCC were strictly observed. Again, the import share of Asia has long run causalities with the import shares of ASEAN and SAARC with GCC. The intra import share of GCC has long run causalities with the import shares of ASEAN and SAARC with GCC and the import concentration index of GCC has long run causalities with the import shares of ASEAN and SAARC with GCC respectively. The intra import share of GCC has short run causalities with import share of Asia, import concentration index of GCC and import share of ASEAN with GCC respectively. The import concentration index has short run causality with the import share of Asia. The import share of SAARC with GCC has short run causality with import share of ASEAN with GCC. The cointegration and vector error correction among Asian GDP, sum of intra export and import shares of GCC, sum of export and import shares of ASEAN with GCC, and sum of export and import shares of SAARC with GCC during 1995-2019 indicated that the GDP of Asia has long run causalities with the sum of intra export and import shares of GCC, the sum of export and import shares of ASEAN with GCC and the sum of export and import shares of SAARC with GCC and even they have short run causalities also. All these observations can justify that GCC has great impact on Asian economic integration process associated with SAARC and ASEAN.